Academic and administration personnel's perceptions of organizational climate (Sample of Educational Faculty of Firat University) - Arabaci, I. Bakir (Elsevier Science Bv, 2010)
The data attempting to determine the perception regarding the organizational climate of the academic and administrative personnel employed at the Education Faculty have been gathered through the scale that was developed by the researcher. As a result of the research, it is found that the faculty employees have mid level organizational climate perception. While the academic and administrative staffs do have problems in participating in decision making, administrative personnel are having problems in communication matters. It is seen that academic personnel have more positive climate perception than administrative personnel, in the same way women and the old have more positive climate perception than men and the young respectively. (C) 2010 Elsevier Ltd. All rights reserved.
2nd World Conference on Educational Sciences (WCES-2010) -- FEB 04-08, 2010 -- Bahceschir Univ, Istanbul, TURKEY
Keywords: Education faculties; academic personnel; administrative personnel; organization climate; perception